Probability of Low Temperature Stress at Different Growth Stages of Boro Rice (Bangladesh Rice Journal, 2016)
CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016.The most sensitive stages of Boro rice against the low temperature are agronomic panicle initiation (API), reduction division (RD) and flowering/anthesis. The critical low temperature is growth stage specific. The time and intensity of the critical low temperature during Boro season has a direct impact on the growth and yield of a crop. Therefore, it is necessary to understand the probability of the critical low temperature with respect to the growth stages to have a good planning for safe harvest. Long term weekly low temperature data have been used to estimate the probability of falling low temperature on those stages and the return period was computed. The growth durations of 1- and 30- November seeded Boro rice crop from 45-day-old seedling of BRRI dhan28 (short duration) and BRRI dhan29 (long duration) are considered to observe the probability. A Boro crop encountering critical low temperature is appeared to suffer from cool injury. The extent of cool injury depends on the nature and duration of low temperature and diurnal change of low (night) and high (day) temperature. The critical low temperature for a rice crop at API, RD and anthesis are 18, 19 and 22°C, respectively. Boro rice is grown between November and May. The low temperature occurs from October to early March. There is, therefore, the probability of low temperature occurrence from the crop establishment to the flowering stage is a great concern. The probability of experiencing stage-wise critical temperature approaches to 100% for early established and short duration crop. However, the late established and long duration crop has the probability little less than the early and short duration crop. In a study it has been observed that short duration BRRI dhan28 having 64.6% sterility to yield 2.5 t ha-1 and BRRI dhan29, 40.8% sterility to yield 6.5 t ha-1. The percentages of corresponding sterility for late established crops were 35.9 and 32.8%. Irrespective of growth duration, the yield is affected a little of the late established crop. Despite low temperature along with the reproductive phase, the late established crop is quite safe due to the parallel high (day) temperature (31-35°C). The high maximum temperature appears to play an important role through the alleviating effect of low temperature. But for early-established particularly short duration variety could not escape the low temperature at some of its sensitive growth stages as the high temperature appears to stay a several degree low (27-29°C) at that time. The low level of high temperature is appeared to drag down the low temperature to aggravate the growth and development of a crop. Therefore, not only the variation of high temperature of the day but also the variation of critical low temperature might have some role in alleviating effect of cool-injury. The periodic return of critical low temperature (10-15°C) during the reproductive stage may occur every year or every alternate year depending on the time across the cropping season and the region as well. Therefore, the critical low temperature, the high temperature during the low temperature period, periodic return of the critical low temperature with respect to growing region and concerned factors should be a consideration for planning a Boro crop.Bangladesh Rice j. 2015, 19(2): 19-27